Education through Mobile Applications on Anemia Knowledge Among Adolescent Girls: A Scoping Review - Mahrorani, Siti Rizkina; Priyatama, Aditya Nanda; Hikmayani, Nur Hafidha (Indonesian Journal of Advanced Research, 2025)
Anemia is a prevalent public health issue affecting adolescent girls globally, significantly impacting their physical health and development. Mobile applications have emerged as a promising tool for health education, potentially improving knowledge and management of anemia. To systematically review and summarize the available literature on mobile applications designed for anemia education among adolescent girls. The review employed the PRISMA-ScR guidelines for scoping reviews to ensure a systematic approach. A total of six articles were reviewed showing that intervention using mobile phone significantly increased the knowledge of adolescent girls compared to the control group (p<0.005) and was effective in preventing anemia. Anemia education use mobile phone applications is effective for increasing nutritional knowledge and preventing anemia in adolescent girls.